Development of Pattern for Supply Chain in Digital for Agricultural Management in a Large Plots in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research was conducted to study and evaluate the pattern supply chain in digital for agricultural management in a large plots in Thailand The samples in the research study consisted of ten purposively selected experts consisted of five experts on supply chain management, five experts on Digital Technology, Data were analysed by arithmetic mean and standard deviation. The research findings model six elements namely namely main components, Farmer group (Producers), Field manager, Finished large plots. Consumers and satisfaction .The assessment of pattern supply chain in digital for agricultural management in a large plots in Thailand using Black-Box technique and The results from experts agreement of pattern supply chain in digital for agricultural management in a large plots in Thailand was a high level. The rating mean of 3.70 and standard deviation of 0.79, which means that the model is appropriate at the high level and applicable to real practice.